1993
DOI: 10.1016/s0006-3495(93)81031-2
|View full text |Cite
|
Sign up to set email alerts
|

The nature of cation-pi binding: interactions between tetramethylammonium ion and benzene in aqueous solution

Abstract: A combined quantum mechanical and molecular mechanical Monte Carlo simulation method was used to determine the free energy of binding between tetramethylammonium ion (TMA+) and benzene in water. The computed free energy as a function of distance (the potential of mean force) has two minima that represent contact and solvent-separated complexes. These species are separated by a broad barrier of about 3 kJ/mol. The results are in good accord with experimental data and suggest that TMA+ binds to benzene more favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Quaternary ammonium compounds also exhibit a preference for aromatic rings (Gao et al, 1993;Ripoll et al, 1993). The occurrence of aromatic phenyl interactions with the R-N+(CH3)3 group has also been noted in crystal structures of small molecules from the Cambridge Structural Database (Verdonk et al, 1993).…”
Section: Charge Interactionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Quaternary ammonium compounds also exhibit a preference for aromatic rings (Gao et al, 1993;Ripoll et al, 1993). The occurrence of aromatic phenyl interactions with the R-N+(CH3)3 group has also been noted in crystal structures of small molecules from the Cambridge Structural Database (Verdonk et al, 1993).…”
Section: Charge Interactionsmentioning
confidence: 83%
“…I I Mrabet et al (1992) showed that Lys -+ Arg mutations in thermostable xylose isomerase (IX) from Actinoplanes missouriensis imparted a significant stability under increasing heat conditions. Quaternary ammonium compounds also exhibit a preference for aromatic rings (Gao et al, 1993;Ripoll et al, 1993). The occur-rence of aromatic phenyl interactions with the R-N+(CH3)3 group has also been noted in crystal structures of small molecules from the Cambridge Structural Database (Verdonk et al, 1993).…”
Section: Charge Interactionsmentioning
confidence: 83%
“…Ibuprofen and omeprazole have aromatic rings, ether, amine and carboxylic groups, responsible for various interactions with the PFP groups (Dougherty, 2007;Martinez & Iverson, 2012). The retention mechanism in reverse-phase chromatography involves various interactions such as π-π interactions, hydrogen bondings, hydrophobic interactions and electrostatic interactions (Aboul-Enein & Ali, 2001b;Gao, Chou, & Auerbach, 1993;Imai, Inoue, Nakanishi, & Kitaura, 2009;Mohan, Vijayalakshmi, Koga, & Suresh, 2010;Ottiger, Pfaffen, Leist, & Leutwyler, 2009;Scrutton & Raine, 1996). This order of elution is very important to predict the mechanism of the separation of these drugs on the reported stationary phase.…”
Section: Mechanism Of Separationmentioning
confidence: 99%
“…[94] A free energy barrier of about 3 kcal mol −1 was predicted between the contact pair and the solvent-separated species. Importantly, it was found that TMA has a greater affinity for benzene than for chloride ions, with a binding constant of 0.8 M −1.…”
Section: Applicationsmentioning
confidence: 99%
“…Importantly, it was found that TMA has a greater affinity for benzene than for chloride ions, with a binding constant of 0.8 M −1. [94] …”
Section: Applicationsmentioning
confidence: 99%